Early Hungarian Information about the Mongol Western Campaign (1235–1242) » - Roman Hautala (Золотоордынское обозрение)
The author of this article examines the origin of the primary information about the Mongol Western Campaign spread in the Kingdom of Hungary on the eve of the Mongol invasion of Eastern Europe. At the beginning of this article, the author pays particular attention to the information on the Mongol expansion, which appeared in the Hungarian Kingdom through the Cumans of southern Moldova. After that the author goes on to consider the earliest news about the beginning of the Mongol Western Campaign delivered to the Hungarian Kingdom by Catholic missionaries as a result of their persistent attempts to find a historic ancestral home of the western Hungarians. The primary information about the beginning of the Mongol Western Campaign was brought to Europe by Dominican Friar Julian, after his return from a journey to the Trans-Volga Magyars in the late 1235. In addition to the valuable description of the Eastern European peoples on the eve of the Mongol invasion, Julian’s report on his first journey to the East contains interesting information about both the early Jochid expansion that preceded the Mongol Western Campaign and the arrival to the land of the Trans-Volga Magyars of the official representative of the Mongol power who informed the Magyars on the completion of the all-Mongolian kuriltai of 1235, which made the decision on the beginning of the Mongol campaign in the West. In turn, the letter of Friar Julian written at the beginning of 1238 is repleted with information about the Mongol tactical warfare, previous military campaigns of Genghis Khan and Jochi, and the first Mongol conquest in the early stages of the Western campaign of Batu. But the most important news brought by Friar Julian in Hungary was an oral report of the Prince of Vladimir on the Mongol plans to attack the Hungarian Kingdom confirming both by the contents of the Batu’s ultimatum and eschatological interpretations of future events.